2020
DOI: 10.36351/pjo.v37i1.1140
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcome of Phacoemulsification Versus Small Incision Cataract Surgery

Abstract: Purpose:  To determine visual rehabilitation of Phacoemulsification in comparison to small incision cataract surgery after implantation of rigid intraocular lens. Study Design:  Quasi Experimental Study. Place and Duration of Study:  Shaheed Mohtarma Benazir Bhutto Medical College Lyari and Sindh Government Lyari General Hospital, Karachi, from July 2018 to December 2019. Methods:  Patients with 35 – 70 years age and diagnosed with senile cataracts and visual acuity of <6/36were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…12,13 The refractive error contributes to poor vision post-operatively. 14,15 while second, the most common reason for an impaired visual outcome is related to posterior capsular rupture (PCR), which was 3.2% in our study, which is comparable with another study conducted on the Pakistani population with PCR results of 3.01%, while few studies mentioned 10% and 11.3%.…”
Section: Discussionsupporting
confidence: 88%
“…12,13 The refractive error contributes to poor vision post-operatively. 14,15 while second, the most common reason for an impaired visual outcome is related to posterior capsular rupture (PCR), which was 3.2% in our study, which is comparable with another study conducted on the Pakistani population with PCR results of 3.01%, while few studies mentioned 10% and 11.3%.…”
Section: Discussionsupporting
confidence: 88%
“…Das et al [9] also observed visual acuity post Small Incision Cataract Surgery and Phacoemulsification for 1 day, 1 month and 6 months. Das et al [9] also observed not only UCVA but also using Best Corrected Visual Acuity (BVCA).…”
Section: Discussionmentioning
confidence: 90%
“…Das et al [9] also observed visual acuity post Small Incision Cataract Surgery and Phacoemulsification for 1 day, 1 month and 6 months. Das et al [9] also observed not only UCVA but also using Best Corrected Visual Acuity (BVCA). Das et al, explained that their research also aims to find out complications of cataract surgery like astigmatism, so they used BVCA examination to see astigmatism.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, the American Academy of Ophthalmology showed no difference in outcomes related to visual acuity after applying foldable or non-foldable lenses in patients with cataract surgery. 16 Narian Das et al 17 reported age of the patients operated for phacoemulsification with foldable lens was from 35 to 70 years Mahesar ML et al 18 reported gender distribution in cataract surgery patients was 48% of males and 39% of females. A study reported 19 prevalence of cataract surgery was higher in women than men with ratio of 1.8% and 1.67% respectively.…”
Section: Gender Distributionmentioning
confidence: 99%